Meningkatkan Kemampuan Anak Mengenal Huruf Melalui Kegiatan Bermain Plastisin - Ratna Dewi; Muhammad Akil Musi; Andi Syahriah (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2022)
This study aimed to describe the child's ability to recognize letters before and after being given plasticine playing activities. This type of research is classroom action research (CAR). This research was carried out in two cycles, and the subjects in this study were group B in TK LKMD Watondo, totaling 16 people. Based on the results of data analysis in the first cycle of 8 aspects, the percentage of achievement reached 57%, while in the second cycle, it increased from 28% to 85%. Thus, it can be concluded that the increase in the ability of children to recognize letters in group B TK LKMD Watondo can be improved through plasticine playing activities.